Introducing Innovation To Undergraduates Through The Engineering Team Project (ETP) Course - Shazi, R. I. (2008)
The overall framework of the Engineering Team Project (ETP) course at Universiti Teknologi PETRONAS is discussed here. ETP is a two hour credit course offered by UTP to all third year engineering students. This group project course involves members from various engineering backgrounds. Such an approach gives students an idea of real-life engineering project work, where multi-disciplinary and cross-functional input is required at many levels. Initially geared towards giving students an early exposure to project implementation, it has been modified to train students on how to be innovative. The basic course structure, assessment methods, the modifications made to train students to be innovative and the results from the modifications are described.